2020
DOI: 10.1101/2020.06.16.155473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homologous chromosomes in asexual rotiferAdineta vagasuggest automixis

Abstract: The several hundreds of species of bdelloid rotifers are notorious because they represent an ancient clade comprising only asexual lineages 1 . Moreover, most bdelloid species have the ability to withstand complete desiccation and high doses of ionizing radiation, being able to repair their DNA after massive genome breakage 2 . To better understand the impact of long-term asexuality and DNA breakage on genome evolution, a telomere-to-tolemere reference genome assembly of a bdelloid species is critical 3, 4 . … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 86 publications
(139 reference statements)
3
14
0
Order By: Relevance
“…Broken down by class and superfamily, the mean values are class I total = 2.09% ± 0.75 (PLEs = 0.59% ± 0.14; LTRs = 0.68% ± 0.26; and LINEs = 0.82% ± 0.47); class II total = 2.79 ± 0.8 (DNA transposons = 2.49% ± 0.77; rolling circles = 0.30 ± 0.11). These results are in broad agreement with previous estimates of TE content in bdelloids (Arkhipova et al, 2017;Flot et al, 2013;Nowell et al, 2018;Simion et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Broken down by class and superfamily, the mean values are class I total = 2.09% ± 0.75 (PLEs = 0.59% ± 0.14; LTRs = 0.68% ± 0.26; and LINEs = 0.82% ± 0.47); class II total = 2.79 ± 0.8 (DNA transposons = 2.49% ± 0.77; rolling circles = 0.30 ± 0.11). These results are in broad agreement with previous estimates of TE content in bdelloids (Arkhipova et al, 2017;Flot et al, 2013;Nowell et al, 2018;Simion et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Broken down by class and superfamily, the mean values are: class I total = 2.09% ± 0.75 (PLEs = 0.59% ± 0.14; LTRs = 0.68% ± 0.26; and LINEs = 0.82% ± 0.47); class II total = 2.79 ± 0.8 (DNA transposons = 2.49% ± 0.77; rolling circles = 0.30 ± 0.11). These results are in broad agreement with previous estimates of TE content in bdelloids [44,46,47,59].…”
Section: Resultssupporting
confidence: 93%
“…Genetic and genomic evidence for their proposed ancient and obligate asexuality remains uncertain, however. Initial evidence of long-term asexuality [43,44] has been refuted by later studies or confounded by alternative explanations [4547]. Some recent studies have proposed alternative modes of inter-individual genetic exchange, but these suggestions would require exotic mechanisms unknown in other animals [44,48], or rates of sex that are difficult to reconcile with the lack of observed males [49].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phased sequencing of A. vaga and hybridization in situ revealed that its 12 chromosomes constitute 6 homologous pairs, a finding interpreted by the authors as evidence of automixis (50). Other recent sequencing found Hardy-Weinberg equilibrium and a fall-off of linkage with distance within a group of 11 isolates of A. vaga, suggested by the authors to be a result of horizontal gene transfer (56).…”
Section: Homologous Chromosome Pairs and Hardy-weinberg Equilibriummentioning
confidence: 96%